2012
DOI: 10.1002/jmri.23754
|View full text |Cite
|
Sign up to set email alerts
|

Combined hepatocellular carcinoma‐cholangiocarcinoma: Report of MR appearance in eleven patients

Abstract: cHCC-CC presents most commonly as a single mass. Five of 11 had MR findings of cirrhosis. Clues to the diagnosis were moderately high signal on T2, portions of tumor that show progressive enhancement/contrast retention, and frequent lack of capsule. Early enhancement patterns included early ring-enhancement and diffuse heterogeneous enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 51 publications
5
30
0
Order By: Relevance
“…Meanwhile, a mixed manifestation of both tumors was not rarely seen, which is also characteristic and highly suggests cHCC-CC. Notably, the HCC-like enhancement pattern displayed with higher percentage in cirrhosis background when comparing with that in noncirrhosis background, partly concurring with de Campos et al [14] who indicated that early enhancement with partial washout on later phases seemed to be the more common enhancement pattern in cirrhotic livers. This may be related to the susceptibility of HCC generation in this specific background and would increase difficulties in differential diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…Meanwhile, a mixed manifestation of both tumors was not rarely seen, which is also characteristic and highly suggests cHCC-CC. Notably, the HCC-like enhancement pattern displayed with higher percentage in cirrhosis background when comparing with that in noncirrhosis background, partly concurring with de Campos et al [14] who indicated that early enhancement with partial washout on later phases seemed to be the more common enhancement pattern in cirrhotic livers. This may be related to the susceptibility of HCC generation in this specific background and would increase difficulties in differential diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…The evolving pathologic definition of this tumor type and the inconsistent use of radiologic terminology to describe it limits the conclusions that can be drawn. A majority of cases report rim APHE with washout appearance in the periphery (86,110,120,(124)(125)(126)(127)(128)(129)(130).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the relative infrequency of these lesions, the evolving pathological definition, and inconsistent use of radiology terminology, provide formidable challenges to accurate analysis of the existing literature. In single‐center, retrospective case reports and series, cHCC‐CCA are described as demonstrating some form of arterial hyperenhancement (APHE), most commonly peripheral or rim‐like, on dynamic contrast‐enhanced magnetic resonance imaging (MRI) and computed tomography (CT; Table ) . Washout appearance is common and is often peripheral in location.…”
Section: Radiologymentioning
confidence: 99%